Trash to treasure: A human beard derived photothermal drug delivery platform for depression therapy. (March 2021) - Zhang, Guoliang; Liu, Xiangfei; Xie, Weichang; Hong, Can; Xu, Yingying; Zhang, Wei; Zhao, Siyu; Xin, Hongbo; Wang, Xiaolei
Highlights: Effective depression therapy has become a global challenge due to the obstacle of blood-brain barrier (BBB). Beard-derived nanoscale particles (BNPs) were first used as the drug delivery platform for depression therapy. The photothermal response capability of BNPs could improve the permeability of BBB and accelerate the drug release. BNPs could neutralize reactive oxygen species (ROS) induced by depression. Abstract: Depression medication is still facing challenges, where the key issue is to explore a desirable delivery platform to assist drugs in penetrating blood-brain barrier (BBB). Herein, we prepared beard nanoscale particles (BNPs) from the beard of young Asian males, which were mainly composed by keratin and melanin. BNPs were able to load antidepressants (Fluoxetine) and exhibited therapeutic effect on depression. Moreover, in vitro and in vivo studies showed that BNPs held favorable photothermal conversion capability, prominent BBB permeability under near-infrared (NIR) irradiation and reliable biocompatibility. Deserved to be mentioned, BNPs also performed a pivotal role in redox equilibrium, which was thus capable of scavenging ROS induced by depression. Subsequently, behavioral and biochemical experiments also demonstrated significant depression-ameliorating effects in vivo . In summary, our data for the first time suggested that biological organism derived beard could serve as ideal low-cost nanovectors for depression therapy. Graphical abstract: Image, graphical abstract